Implementation of Email System With Steganography - Nisar, Uzair; Stewart, Craig (International Journal of Computer Sciences and Engineering, 2019)
Email Systems are widely used as the means of communication. Organizations in order to seek more security tend to lean towards more secure ways of communication. This project facilitates the means of communication in a more secure format. The system being developed uses the technique called ‘Steganography’. Steganography hides the data behind an image so any intruder or hacker can only see the image and not the critical data. This is the secure means of sending information. To make it even more secure the steganographic image is then protected by a password using the technique called ‘Cryptography’. This can be implemented by developing 3 tools, first of which will hide data behind image, then the next tool encrypts it with a password and the final tool is used to send it over internet. This system will not only provide the best secure communication of data but it also makes the use of three different tools embedded in a single system.